Comparing CEO compensation effects of public and private acquisitions - James A. Brander; Edward J. Egan; Sophie Endl (Journal of Risk and Financial Management, 2021)
We estimate the effect of acquisition performance and acquisition activity on CEO compensation for the full set of CEOs of large public U.S. corporations in the Execucomp database over the period 1992-2016. Most previous work has focused on publicly traded acquisition targets. We focus on the comparison between public and private targets, showing significant differences between the two. One primary finding, based on panel data regressions (using both fixed and random effects) is that the performance of private acquisitions, as measured by abnormal announcement returns, has a statistically significant positive effect of plausible economic magnitude on CEO compensation. Public acquisitions exhibit a smaller positive effect that is statistically insignificant. For both, acquisition activity (number of acquisitions) has a statistically significant positive effect on compensation. Our main results suggest that agency considerations are important for both public and private acquisitions but are more important for public acquisitions.
Keywords: 330; acquisitions; CEO incentives; executive compensation; private equity